2008
DOI: 10.1016/j.ajog.2007.05.033
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene and other carotenoid intake in relation to risk of uterine leiomyomata

Abstract: Objective-Carotenoids have antioxidant properties and have been associated with reduced risks of some cancers. We hypothesized that carotenoid intake may reduce the risk of diagnosed uterine leiomyoma (UL).Study design-We evaluated the associations between dietary carotenoids and risk of diagnosed UL in 82,512 premenopausal women ages 26-46 in 1991 in the Nurses' Health Study II over ten years of follow up. Diet was assessed every four years with a validated food frequency questionnaire, and incidence of UL wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
16
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 28 publications
6
16
1
Order By: Relevance
“…In a study on the relationship between using Lycopene, Carotene and uterine myoma, done by Catherin Trey et al (2008), it was found that in smokers who used Carotene, the probability of diagnosing uterine myoma is more than other people. that is not in agreement with our study (14).…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…In a study on the relationship between using Lycopene, Carotene and uterine myoma, done by Catherin Trey et al (2008), it was found that in smokers who used Carotene, the probability of diagnosing uterine myoma is more than other people. that is not in agreement with our study (14).…”
Section: Discussioncontrasting
confidence: 57%
“…Paradoxical results were seen in some studies investigating the effect of nutrition on leiomyoma. In a study done in 2008, there was no relationship between consumption of carotenoid-containing foods and leiomyoma (14). In a similar study in America in 2008, there was found no relationship between the diet in general, high-fiber diet, soya and leiomyoma but in this study, drinking alcohols increased leiomyoma (15).…”
Section: Introductionmentioning
confidence: 50%
“…In tomato, LCY-B is considered an important carotenogenic gene that codifies a crucial enzyme involved directly in the synthesis of α-carotene and β-carotene through the cyclization of lycopene (Moreno et al, 2013). As the most powerful antioxidant in the carotenoid family, lycopene plays an important role in the prevention of cancer and chronic diseases (Rao and Agarwal, 2000;Terry et al, 2008). Tomato carotenoids are beneficial not only for human health but also for major breeding traits such as fruit color (Gady et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, higher frequencies of tumors stood out among black women 4,[23][24][25][26] , those exposed to factors associated with the increase in ovarian hormones (estrogen and progesterone), those undergoing hormonal therapy 27 , those consuming greater amounts of red meat and sausages 28 , those aged between 40 and 50 years 4,29 , those who had had an early menarche [30][31][32] , those with a high BMI 31,[33][34][35][36] and fat percentage 37 , and those with an increase in weight during adulthood 33,34,38 . On the other hand, lower frequencies of tumors were found in women who practiced physical activities 39 , smokers 30,33,40,41 , those with a higher number of children [30][31]36,42 , those who had reached menopause 36 and those who consumed greater amounts of fruits, vegetables and fish 28,35 . Whereas studies conducted in the United States indicate prevalences of up to 80%, depending on the characteristics of the sub-groups studied, European studies have revealed significantly lower prevalences of tumors 43 .…”
Section: Introductionmentioning
confidence: 99%